The “Salt of the Earth” documentary film by Wim Wenders as an implementation of the „text within a text” rhetorical strategy - Fiołek-Lubczyńska, Bogumiła (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
Wim Wenders’s report is devoted to the output of the world-renowned photographer Sebastião Salgado. The presentation of his works in the documentary employed the text within a text composition, or rather „photography within a documentary”. The director emphasised the photographs and the statements by the photographer in such a way that the viewers could learn about Salgado as the author of his works and as a human, a humanist concerned about the fate of contemporary human beings. The analysis and the interpretation of the report enabled me to reflect theoretically on the definition and the specificity of photography.